Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T20:41:40+01:00
A) x²+6x+9=0
a=1 b=6 c=9
Δ=b²-4ac
Δ=6²-4*1*9
Δ=36-36
Δ=0
x₁=-b²/2a
x₁=36/2
x₁=18

b)3x²+2x-2=0
a=3 b=2 c= -2
Δ=b²-4ac
Δ=2²-4*3*(-2)
Δ=4+24
Δ=28
√Δ=√28=√4*6=2√6
x₁=-b²+√Δ/2a
x₁=4+2√6/6
x₂=-b²-√Δ/2a
x₂=4-2√6/6

c) 2x=5x²+1
5x²-2x+1=0
a=5 b=-2 c=1
Δ=b²-4ac
Δ=4-20
Δ=-16
brak rozwiązania

d) -x²+2x+24<0
a=-1 b=2 c=24
Δ=b²-4ac
Δ=4+96
Δ=100
√Δ=10
x₁=-b²+√Δ/2a
x₁=4+10/-2
x₁=14/-2
x₁=7
x₂=-b²-√Δ/2a
x₂=4-10/-2
x₂=-6/-2
x₂=3

e) x²-4x+8≤0
a=1 b=-4 c=8
Δ=b²-4ac
Δ=16-32
Δ=-16
brak rozwiązania

f) 3x+7≥4x²
-4x²+3x+7≥0
a=-4 b=3 c=7
Δ=b²-4ac
Δ=9+112
Δ=121
√Δ=11
x₁=-b²+√Δ/2a
x₁=9+11/-8
x₁=20/-8
x₂=-b²-√Δ/2a
x₂=9-11/-8
x₂=-2/-8
x₂=¹/₄